2020
DOI: 10.1186/s13104-020-05341-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances among physicians during COVID-19 pandemic

Abstract: Objectives To assess prevalence and related factors of sleep disturbances among Saudi physicians during COVID-19 pandemic. Data were collected through a questionnaire including items about demographic characters, knowledge about covid-19 and items to assess sleep quality that were extracted from Pittsburgh Sleep Quality Index (PSQI) scale. Results Prevalence of sleep disorders was 43.9%, doctors in the age group of 31–40 years, associate consultants had a significant higher prevalence of sleep disorders. Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 35 publications
3
40
0
6
Order By: Relevance
“…A total of 34 studies were included, with the subjective sleep quality being assessed by using self-reported questionnaires 4 , 37–69 ( Table 4 ). The prevalence of poor sleep quality in HWs during COVID-19 pandemic ranged from 18.4% to 84.7% based on scores of PSQI, 4 , 37–47 which were comparable to that before the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 34 studies were included, with the subjective sleep quality being assessed by using self-reported questionnaires 4 , 37–69 ( Table 4 ). The prevalence of poor sleep quality in HWs during COVID-19 pandemic ranged from 18.4% to 84.7% based on scores of PSQI, 4 , 37–47 which were comparable to that before the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Physicians working more days, with higher patient volumes, or with increased duties than before than pandemic also had an increased prevalence of psychological symptoms [ 96 , 101 , 122 , 128 , 149 , 187 , 192 , 195 , 198 ]. Eighteen studies reported on insomnia [ 32 , 35 , 36 , 54 , 65 , 69 , 88 , 114 , 128 , 145 , 149 , 163 , 175 , 177 , 181 , 188 , 192 , 194 ], which is associated with psychiatric disorders and is a risk factor for depression and anxiety [ 15 , 32 , 54 , 65 , 69 , 199 , 200 ]. During the SARS outbreak, physicians of Asian descent felt more stigmatized than their Caucasian colleagues (Canada) [ 15 , 32 , 35 , 36 , 46 , 54 , 65 , 69 , 88 , 114 , 128 , 145 , 149 , 163 , 175 , 177 , 181 , 188 , 192 , 194 , 199 , 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…One hundred studies reported on factors associated with psychological symptoms during infectious disease outbreaks. Female sex (compared to male) was the factor most commonly associated with worse psychological symptoms in physicians [30,41,44,48,63,66,71,77,89,98,112,122,127,128,138,142,144,148,163,165,170,[174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189]. Other factors associated with poorer psychological outcomes included direct patient contact [28, 32, 34, 44, 46, 53, 59, 64, 71, 81, 95, 98, 112, 122, 130, 163, 169, 175, 182, 183, 186, 190-192] [30, 34, 41, 44, 48, 59, 63, 66, 71, 77, 89], single marital status (compared to married) [39,44,59,63,98,122], younger age [33,…”
Section: Factors Associated With Psychological Symptoms During Infectious Disease Outbreaksmentioning
confidence: 99%
See 1 more Smart Citation
“…Both emotional responses and sleep disturbances may be related to the current COVID 19 pandemic, where isolation measures, in addition to the workload, affect health professionals. Due to the burden of stress generated, sleep deprivation, little contact with their family, long hours, and concern for the future, healthcare workers could experience a decrease in their immune response and a lower response to future outbreaks in this sector of the population where COVID 19 has already claimed many victims ( Alnofaiey et al, 2020 ; Conroy et al, 2021 ). These situations have already been explored in other types of populations ( Dubey et al, 2020 ; Liem et al, 2020 ; Rajkumar, 2020 ; Rashidi Fakari and Simbar, 2020 ; Yang et al, 2020 ; Yao et al, 2020 ; Zhu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%